PENGARUH SOLVABILITAS, PERTUMBUHAN ASET, FIRM SIZE, DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTURDI BEI TAHUN 2018-2020 - Erric Pamella Dhova; Muhammad Gunawan Setyadi; Suprihati Suprihati (Jurnal Akuntansi dan Pajak, 2022)
Dividend policy is a policy in determining the use of profits earned by the company, whether to be distributed to shareholders or to be retained in the form of retained earnings for investment purposes. Company management needs to consider various factors to make decisions regarding dividend distribution in order to achieve an optimal dividend policy. The purpose of this study was to analyze the effect of solvency, asset growth, firm size, and profitability have an influence on the company's dividend policy. This study uses empirical methods using secondary data obtained from the Indonesia Stock Exchange. The population of this study were all companies listed on the Stock Exchange, while the sample of this study were 32 companies selected by purposive sampling method. The data used is the period 2018 - 2020 obtained from the Indonesian Directory Exchange in 2022. The data analysis method used is the multiple linear regression method, t test, F test, coefficient of determination test (Adjusted R2), and is accompanied by classical assumption testing. The results of the study concluded that: Solvency has no effect on the Dividend Payout Ratio; Asset Growth has an effect on the Dividend Payout Ratio; Firm Size has no effect on the Dividend Payout Ratio; Profitability affects the Dividend Payout Ratio; Solvency, Asset Growth, Firm Size, and Profitability have a simultaneous effect on the Dividend Payout Ratio. Keywords: Dividend, Solvency, Asset Growth, Size, Profitability